OPTIMALISASI DAYA LUARAN PANEL SURYA DENGAN SISTEM PENCARIAN INTENSITAS MATAHARI OPTIMAL DENGAN KONTROL FUZZY - Sitepu, Fredrik; Dalimunthe, Muhammad Erpandi; Anisah, Siti (Jurnal Informatika dan Teknik Elektro Terapan, 2024)
To optimize the performance of sun tracking systems, adaptive and intelligent control techniques are required. One effective method for dealing with systems that have high uncertainty and non-linearity is fuzzy control. Fuzzy control has several advantages over conventional control methods, such as the ability to handle a variety of changing operating conditions and flexibility in application to various types of systems. By implementing fuzzy control, the sun tracking system can operate more efficiently, dynamically adjusting the tilt angle of the solar panels to obtain optimal sunlight intensity. In addition, the results of this research are expected to provide practical and applicable solutions for the development of renewable energy technology, especially in developing countries which have great potential for utilizing solar energy. Thus, this research has high urgency in the global and local context. . Optimizing the output power of solar panels through sun tracking systems with fuzzy control can be an important step towards a more sustainable, efficient and environmentally friendly energy system.